Association of prenatal alcohol exposure with preadolescent alcohol sipping in the ABCD study®. (1st September 2020) - Lees, Briana; Mewton, Louise; Stapinski, Lexine A.; Teesson, Maree; Squeglia, Lindsay M.
Highlights: Any prenatal alcohol exposure increased risk of alcohol experimentation by ages 9–10. Linear association found for levels of exposure and likelihood of sipping alcohol. Results were consistent when adjusting for known confounding factors. Prenatal alcohol exposure is a modifiable risk factor for early alcohol use. Abstract: Background: Early alcohol use initiation is one of the strongest predictors of alcohol use disorders. Identifying modifiable risk factors for problematic alcohol use can guide prevention initiatives. Globally, approximately 10% of women consume alcohol during pregnancy, however the impact of prenatal alcohol exposure (PAE) on offspring alcohol use patterns has been understudied. The aim of this study was to examine associations between PAE and preadolescent alcohol use behaviors. Methods: Cross-sectional data were utilized from 10, 119 children aged 9.0–10.9 years (M = 9.9, SD = 0.6) enrolled in the Adolescent Brain Cognitive Development Study®, based in the United States. Linear mixed models tested associations between PAE and endorsement of non-religious alcohol sipping in offspring, when adjusting for confounding factors. Results: In total, 2675 (26.4 %) youth were prenatally exposed to alcohol. Among PAE youth, total standard drinks consumed during pregnancy ranged from 0.4–90.0 drinks (M = 26.8, SD = 24.5). Compared to unexposed youth, those with any alcohol exposure during early pregnancy (∼0−7 weeks) were 1.7 times (95 % CI 1.4–2.0, p < .0001) more likely to endorse sipping alcohol by ages 9–10, while youth with low-level doses of alcohol throughout the entire pregnancy were 2.9 times (95 % CI 1.9–4.6, p < .0001) more likely to endorse sipping, when adjusting for confounding factors. A dose-dependent association between total standard drinks consumed during pregnancy and youth sipping endorsement was observed (β = 0.2, 95 % CI 0.1–0.2, p < .0001) . Conclusions: This study shows that any alcohol use during pregnancy may play an important role in very early alcohol use experimentation among offspring by ages 9–10.